Cardiac Fibrosis Attenuation by Chlorogenic Acid and Epigallocatechin-Gallate Mediated by Suppression of Galectin-3 Gene Expression and Collagen Deposition in Rat Metabolic Syndrome Model - Indah Nur Chomsy; M. Saifur Rohman; Mifetika Lukitasari; Dwi Adi Nugroho; Husnul Khotimah (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: Metabolic syndrome (MetS) is a set cluster of risk factors for metabolic abnormalities thatcan develop cardiovascular disease (CVD), one of that is remodeling or cardiac fibrosis. Cardiac fibrosisidentified from the high levels of the profibrotic molecule; one of them is galectin-3. Aim: This studyintended to determine the effect of combination therapy of green coffee (CGA) and green tea (EGCG) oncardiac fibrosis by raise of the galectin-3 gene expression and collagen deposition in rat cardiac tissue inthe rat metabolic syndrome model. Methods: Twenty-four male MetS rats (Sprague-Dawley) divided intotwo control groups and three groups therapy (n=5) administration of the CGA 200mg/kgbw (body weightin kilograms) and EGCG 300mg/kgbw orally. After eight weeks of treatment, rats euthanized, then mRNAexpression of galectin-3 was measured. Furthermore, collagen deposition of cardiac tissue carried out inhistology slides. Results: Research reveals that the expression of galectin-3 decreased in the metabolicsyndrome model group, which given combination therapy compared with metabolic syndrome model micethat did not receive any therapy (P=0.000). Collagen deposition in cardiac tissue also found less than inthe therapy group compared with the group not treated with both compounds (P=0.000). The correlationbetween the two parameters shows a positive association with low strength. Conclusion: This study showsthat the combination therapy of CGA and EGCG is an engaging therapeutic candidate. It expected to reducethe progression of cardiac fibrosis in metabolic syndrome